2013
DOI: 10.1186/1754-6834-6-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of alkaline pretreatment parameters for corn stover enzymatic saccharification

Abstract: BackgroundPrevious research on alkaline pretreatment has mainly focused on optimization of the process parameters to improve substrate digestibility. To achieve satisfactory sugar yield, extremely high chemical loading and enzyme dosages were typically used. Relatively little attention has been paid to reduction of chemical consumption and process waste management, which has proven to be an indispensable component of the bio-refineries. To indicate alkali strength, both alkali concentration in pretreatment sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(125 citation statements)
references
References 28 publications
11
110
0
4
Order By: Relevance
“…A high SF led to substantial loss of hemicellulose, facilitated degradation of hexose and pentose sugars to weak acids and furan derivatives (Chen et al 2013b). Baral et al (2014) reviewed the effects of SF on sugar production and corresponding inhibitor formation for the most common pretreatment processes, specifically with corn stover as a substrate.…”
Section: Role Of Particle Size and Severity Factormentioning
confidence: 97%
See 1 more Smart Citation
“…A high SF led to substantial loss of hemicellulose, facilitated degradation of hexose and pentose sugars to weak acids and furan derivatives (Chen et al 2013b). Baral et al (2014) reviewed the effects of SF on sugar production and corresponding inhibitor formation for the most common pretreatment processes, specifically with corn stover as a substrate.…”
Section: Role Of Particle Size and Severity Factormentioning
confidence: 97%
“…Therefore, determining the optimum particle size can yield more sugars and, subsequently, reduce inhibitors as well as preparation costs. Researchers have used 0.5-25 mm particle sizes for corn cobs and stover (Chen et al 2013b;Gao et al 2012;Liu et al 2013a;Mu et al 2011;Qin et al 2012;SU Donghai et al 2006;Um and van Walsum 2012;Yoo et al 2013; and are trying to identify optimum size for a particular substrate. Recently, Liu et al (2013b) reported variations in sugar production and process toxicity with respect to particle size during steam explosion pretreatment (200°C for 5 min) of corn stover.…”
Section: Role Of Particle Size and Severity Factormentioning
confidence: 98%
“…Previous studies conducted on different biomass have reported that lime pretreatment shows relatively high yield of reducing sugars after enzyme hydrolysis in comparison to other pretreatments [19,20]. Researchers have investigated high concentration of acid and alkaline at higher temperature and pressure condition to obtain better pretreatment efficiency of the biomass [21,22].…”
Section: Effect Of Hemp Biomass Saccharificationmentioning
confidence: 98%
“…In addition, biomass could release acid compounds such as acetic acid in high-temperature processing which could be employed as the catalyst for autohydrolysis (Garrote et al, 2007). The most commonly used base was NaOH (Chen et al, 2013).…”
Section: Catalystmentioning
confidence: 99%